High-field phase diagram of Ni3V2O8 studied by specific heat and magnetocaloric effect measurements. (28th April 2021) - Dong, C; Kohama, Y; He, Z Z; Han, X T; Sato, K; Matsuo, A; Kindo, K; Yang, M; Wang, J F
Abstract: The H – T phase diagram of Ni3 V2 O8 is very rich and remains puzzling in a high magnetic field range. Through the state-of-the-art specific heat measurement in pulsed high field to 35 T and magnetocaloric effect measurement up to 45 T, we successfully construct the high-field phase diagram of Ni3 V2 O8 for fields applied along the b axis. The phase boundaries are corrected for previous results by magnetization and magneto-optical measurements. The resulting phase diagram shows that the high temperature incommensurate (HTI) phase develops well to high fields and low temperatures. In addition to the early reported C′, C, low temperature incommensurate (LTI) and HTI phases, we explore a new magnetic ordered phase called HF1 in fields of 10–30 T. A multicritical point is also observed at 6 K and 8 T. Furthermore, the specific heat data reveal enhancements of the anomalies at ∼4 K, probably associated with a strong spin–lattice coupling in this frustrated multiferroic material.